1985
DOI: 10.1093/ije/14.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution and its Effect on Pulmonary Function of Adult Non-Smoking Women: I. Exposure Estimates for Nitrogen Dioxide and Passive Smoking

Abstract: The potential effects of indoor NO2 and tobacco smoke on the respiratory system were studied using pulmonary function data from a longitudinal study. In 1982, NO2 was measured in 163 homes of non-smoking adult women and detailed information on smoking inside the house was gathered over the period 1965-1982. Personal exposure to NO2 was calculated from the measured levels and the activity pattern of the study population (range 11-139 micrograms NO2/m3). Historical exposure was estimated using regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This is in line with previous Dutch NO 2 monitoring studies, which have shown that these kinds of water heaters are a major source of indoor NO 2 in the Netherlands (17,18). For example, Fischer et al (18) found an estimated difference in personal NO 2 between women living in homes with and without a gas water heater of 24 µg/m 3 in the case of an unvented water heater and 12 µg/m 3 in the case of a vented gas water heater.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with previous Dutch NO 2 monitoring studies, which have shown that these kinds of water heaters are a major source of indoor NO 2 in the Netherlands (17,18). For example, Fischer et al (18) found an estimated difference in personal NO 2 between women living in homes with and without a gas water heater of 24 µg/m 3 in the case of an unvented water heater and 12 µg/m 3 in the case of a vented gas water heater.…”
Section: Discussionsupporting
confidence: 92%
“…Because of the known strong influence of unvented gas water heaters on indoor NO 2 concentrations in the Netherlands (17,18), children whose parents reported that they had such a water heater were excluded from the analysis. Combined analysis of data from all four seasons was performed using a multiple regression model in which three dummy variables for each season were included.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of other chemical pollutant exposures on the incidence of asthma is not sufficiently known. However, it is known that aeroallergens are strongly associated [8,249]. There are also some low molecular weight chemicals [171,172,293] and certain metals, such as chromium and nickel (WHO EHCs) which can, with significant exposures, produce asthma.…”
Section: Chronic Respiratory Morbiditymentioning
confidence: 99%
“…Homes without a kitchen geyser served as the reference category; gas fired kitchen water heaters are major sources of NO 2 in Dutch homes. 4 Virtually all homes were equipped with gas cookers, so that it did not make sense to include the presence of gas cookers as an exposure variable. b.…”
Section: Discussionmentioning
confidence: 99%